PENGARUH LITERASI KEUANGAN, SIKAP KEUANGAN, PENDAPATAN, DAN TINGKAT PENDIDIKAN TERHADAP PERILAKU PENGELOLAAN KEUANGAN KELUARGA - Ilmiyah Nur Azizah Ilmiyah; Bagus Hari Sugiharto; Intan Oktaviana Jumai; Febri Falisa; Audry Shatara; Rita Mutiarni (STIE PGRI Dewantara Jombang, 2025)
Problems in family financial management in Indonesia still shows a collapse of priorities, where many families perceive low difficulty in meeting basic needs and education costs, but prefer to allocate funds for symbolic consumption such as purchasing gold. This condition reflects low financial literacy, irrational financial attitudes, and still low levels of education. The purpose of this study was to examine the impact of financial literacy, financial attitudes, income, and education level on family financial management behavior in Sukolelo Village, Prigen District, partially and simultaneously. The research method used was quantitative with a purposive sampling technique. The results showed that education level had a negative and insignificant effect on family financial management behavior. Meanwhile, financial literacy, financial attitudes, and income had a significant positive effect on family financial management behavior. It can be concluded that education does not always determine the ability to manage finances.